Picasso and the art of drawing - Lloyd, Christopher 1945- (Modern Art Press, 2018)
In this generously illustrated and lively book, Christopher Lloyd sets out and interprets the lifelong achievement of Picasso (1881–1973) as a draftsman. Although there have been many publications about his drawings that have tended to focus on particular periods of his career, this stunning volume specifically examines how drawing serves as the vital thread connecting all of Picasso’s art, just as it also links his private world with his public persona of which he was becoming increasingly aware in his later years. Picasso and the Art of Drawing ultimately showcases how the basis of the titular artist's style as painter, sculptor, printmaker, and designer was manifestly achieved through drawing.--Provided by publisher.